A bibliography of rice literature translations available in the International Rice Research Institute Library and Documentation Center - Alluri, Fe M.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1976)
This bibliography is a compilation of all the rice literature translations available in the International Rice Research Institute (IRRI) Library and Documentation Center as of October 1975. It is arranged alphabetically by author. In the case of entries with no authors, they are entered under the title. Each entry is provided with an item number, from 1-914. This is the number referred to in the keyword index to facilitate the location of specific items.
Each translation entry includes the following information: author and title of article, title of periodical or book where it was taken, volume number, issue number if available, pagination and the date of publication. The name or names of translators are also included in all the entries whenever this information is present in the translations examined. Also added in the right hand corner of every entry is the number assigned by IRRI Library.
A keyword index is provided at the end of the bibliography.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Rice--Bibliography.